Cystatin C, mortality risk and clinical triage in US adults: threshold values and hierarchical importance - Foley, Robert N. (Oxford University Press, 2011)
Background. It has been suggested that cystatin C may be a superior measure of estimated glomerular filtration rate (eGFR) than creatinine-based methods. We aimed to assess the utility of cystatin C for clinical triage in community-based settings. Methods. We identified cystatin C thresholds that maximize sensitivity and specificity (Max(Sn) (+) (Sp)) for predicting death and subsequently applied classification tree methodology considering serum creatinine, creatinine-based eGFR, urinary albumin–creatinine ratio and conventional modifiable risk factors to define subgroups, interactions and hierarchical ranks in fasting US adults (National Health and Nutrition Examination Survey 1988–94, followed through 2006). Results. A threshold cystatin C value of 0.94 mg/L exhibited the best maximum combined value of sensitivity and specificity for predicting death (Max(Sn) (+) (Sp), Sn 0.64/Sp 0.78). When all variables were considered jointly in a classification tree, cystatin C and albumin–creatinine ratio were the primary mortality discriminators in subgroups that added up to 41 and 14% of the study population, respectively; serum creatinine and creatinine-based eGFR were non-discriminatory. Conclusion. Cystatin C may be useful for risk-based clinical triage in public health settings.